Financial Reporting in Japan (Book). - Burns, Thomas J.; Lowe, Howard D. (The Accounting Review, 1978)
Abstract Reviews the book "Financial Reporting in Japan," by Robert J. Ballon, Iwao Tomita and Hajime Usami.